Safety and tolerability of intramuscular sotrovimab administered at different injection sites: results from the Phase 1 COSMIC study - Jennifer Moore; Alicia Aylott; Wen-Hung Chen; Jerzy Daniluk; Ian A. Hawes; Sergio Parra; Prosenjit Sarkar; Yasmin Sanchez-Pearson; Megan Turner; Amanda Peppercorn; Andrew Skingsley (mAbs)
Monoclonal antibodies (mAbs) administered using intramuscular (IM) injections could offer a convenient and accessible therapeutic option. However, there is a paucity of data on IM tolerability by injection site to guide mAb development. This Phase 1, open-label trial randomized healthy adults to receive 62.5 mg/mL sotrovimab IM into each dorsogluteal muscle (2 × 4 mL injections), or 100 mg/mL sotrovimab IM into the dorsogluteal muscle (1 × 5 mL), the anterolateral thigh muscle (1 × 5 mL) or each deltoid muscle (2 × 2.5 mL). Incidence of adverse events (AEs), serious AEs (SAEs) and AEs of special interest (AESIs) were assessed, along with patient-reported outcomes (Perception of Injection version 3 questionnaire and Pain-Numeric Rating Scale [Pain-NRS]). Of 329 participants screened, 215 (65%) received sotrovimab (median age 39 [range 19–65] years; 57% female; mean body mass index 25.4 kg/m2). Overall, 46% (n = 99/215) of participants reported AEs; the most common was injection site pain (30%; n = 65/215). There were no SAEs reported, and all AESIs were Grade 1 or 2. Through Day 8, mean Pain-NRS values were < 1 and similar across injection sites; values were highest on Day 1 at 15 minutes post-dosing and decreased over time through Day 8. Injection site reactions were reported by all participants as ‘not at all’ or ‘a little’ bothersome. No or little impact on sleep and movement was reported. Sotrovimab IM was generally well tolerated at all injection sites, at volumes up to 5 mL (dorsogluteal and anterolateral thigh) and as one 2.5 mL injection into each deltoid muscle. To our knowledge, these are the first data to show that a >2 mL mAb injection into each deltoid muscle is well tolerated.Trial registration ClinicalTrials.gov identifier, NCT05280717